Une bibliothèque de médecine à travers le temps. La Collection du Dr Jean-Guy Provost - Provost, Anne; Trudel, Normand; Bouchard, Éric (Anne Provost, 2014)
Keywords: Médecine

Histoire de la médecine au Québec, 1800-2000. De l'art de soigner à l'art de guérir - Goulet, Denis; Gagnon, Robert (Septentrion, 2014)
Keywords: Hôpitaux; Médecine; Université McGill; Université de Montréal

Medical Genetics at McGill: The History of a Pioneering Research Group - Canning, Christopher; Weisz, George; Tone, Andrea; Cambrosio, Alberto (Bulletin canadien d'histoire de la médecine / Canadian Bulletin of Medical History, 2013)
Number: 1
Keywords: Médecine; Université McGill

Le règne de la scientificité: histoire de l'étiologie des maladies infectieuses dans la presse médicale du Québec, 1840-1880 - Beaudry, Louka (Université de Montréal, 2013)
Keywords: Médecine

The Medicalization of Stress: Hans Selye and the Transformation of the Postwar Medical Marketplace - Burrows, Vanessa (The City University of New York, 2015)
Keywords: Médecine; Selye; H.

Medicine Advertising, Women's Work, and Women's Bodies in Montreal Newspapers 1919-39 - Baillargeon, Denyse (Consuming Modernity: Gendered Behaviour and Consumerism before the Baby Boom, 2013)
Translators: _:n47334
Keywords: Femmes; Médecine; Publicité

Préparer la révolution psychiatrique depuis Paris: Camille Laurin et l’histoire médicale française au service de la réforme du système québécois de santé mentale - Klein, Alexandre (Revue d'histoire de l'Amérique française, 2018)
issued: 2018-24-00/2018-21-00
Keywords: Histoire; Hôpitaux psychiatriques; Médecine

Designing the Medical Museum - Adams, Annmarie (Healing Spaces, Modern Architecture, and the Body, 2018)
Keywords: Musées; Médecine; Université McGill

Histoire scientifique du Plateau (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-23-00
Keywords: Géologie; Institut des sourdes-muettes; Institut des sourds-muets; Médecine; Sourds

Encountering Maude Abbott - Adams, Annmarie (Feminist Encounters: A Journal of Critical Studies in Culture and Politics, 2018)
Number: 2
Keywords: Abbott; Maude E.; Femmes; Histoire; Hôpitaux; Musées; Médecine; Royal Victoria Hospital; Université McGill

L'Église catholique à travers Mes Tablettes, journal intime de Romuald Trudeau, 1820-1850 - Roy, Fernande (Études d'histoire religieuse, 2010)
Homme politique, commerçant, médecin et pharmacien. (Journal)
Number: 76
Keywords: Apothicaires; Trudeau; Romuald